Parasitismo por microsporidios (Microspora) en tres especies de mosquitos (Diptera: Culicidae) de la Argentina - Micieli, María V.; García, Juan J. (Revista de Biología Tropical, 1996)
Three microsporidia species were found infecting mosquito larvae from two argentine province: Amblyospora sp. in P.wrophora c)lmescens, Amblyospora sp in P. varinervis and Parathelohani sp. in Anopheles triannulatus. These microsporidia were distinguished on the basis of meiospore shape and size, and presumed host specificity.